PENGARUH KUALITAS PELAYANAN DAN DISIPLIN KERJA TERHADAP KEPUASAN PELANGGAN PADA PT. POS INDONESIA (PERSERO) SUMENEP - Aulia Fatonah , Mirza; Rusnani, Rusnani (LP2M Universitas Bina Bangsa, 2025)
PT. Pos Indonesia Persero is required to be able to provide good service and work discipline to consumers or customers, this aims to produce high customer satisfaction so that consumers are interested in using post office services again. The purpose of this study is to determine the Influence of Service Quality and Work Discipline on Customer Satisfaction at PT. Pos Indonesia (Persero) Sumenep.This research was conducted at PT. Pos Indonesia Persero Sumenep. The method used in this study is a quantitative method with a sample of 90 respondents. The sampling analysis technique uses the Non-Probability Sampling method with the data collection technique Accidental Sampling by distributing questionnaires. The data analysis techniques used are data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. From the results of the tests and analyses carried out, it was stated that the quality of service had a positive and significant effect on customer satisfaction at PT. Pos Indonesia Persero Sumenep, work discipline has a positive and significant effect on customer satisfaction at PT. Pos Indonesia Persero Sumenep, simultaneously service quality and work discipline affect customer satisfaction at PT. Pos Indonesia Persero Sumenep